Radar Data for Identifying the Characteristics of Tropical Forest Stands - Agus Wuryanta (Forum Geografi, 2016)
Radar is one of remote sensing technology which utilizes active electromagnetic energy and are able to provide information about the characteristics of forest stand. This study utilized JERS-1 and ERS-1 radar images to analyze the relationship between the radar backscatter and forest stand characteristics such as Diameter Breast Height (DBH), basal area, and canopy cover. This research was conducted in Jambi Province, Bungo Tebo District, Sumatra, Indonesia. The research site covered the forest concession, Suku Anak Dalam, the area adjacent to Pelepat and Batang Tebo River, and Kuamang Kuning village. Gamma Map Filter with 7 x 7 window size was applied to reduce speckle noise of the SAR images (ERS-1 and JERS-1). This study found out the positive significant correlation between basal area and DBH with JERS-1 radar backscatter (i.e., r = 0.75 and r = 0.70), while ERS-1 radar backscatter has correlation (r = 0.64) with the canopy cover.